2004
DOI: 10.1038/sj.onc.1207189
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of BRAF and KRAS2 in the development of Barrett's adenocarcinoma

Abstract: Activation of the Raf/MEK/ERK (MAPK) signal transduction cascade by RAS mutations has been found in a variety of human cancers. Mutations of BRAF provide an alternative route for activation of this signalling pathway. To determine the role of mutations in BRAF and KRAS2 in the neoplastic progression of Barrett's adenocarcinoma, we analysed both genes for common mutations. After microdissection, DNA of 19 Barrett's adenocarcinomas, 56 Barrett's intraepithelial neoplasias (n ¼ 29 low-grade intraepithelial neopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 25 publications
2
45
0
2
Order By: Relevance
“…To minimize the chance of PCR amplicon contamination pre-and post-PCR rooms were strictly separated, and we used a direct PCR to avoid pseudogene amplification rather than nested PCR for KRAS mutation detection. 37,38 Another factor to consider is tumor heterogeneity. In samples with lower tumor percentage and low amount of the mutated allele, automated Sanger sequence analysis could miss variants, whereas HRM could still detect mutations in gDNA and wgaDNA from samples with low tumor percentages.…”
Section: Discussionmentioning
confidence: 99%
“…To minimize the chance of PCR amplicon contamination pre-and post-PCR rooms were strictly separated, and we used a direct PCR to avoid pseudogene amplification rather than nested PCR for KRAS mutation detection. 37,38 Another factor to consider is tumor heterogeneity. In samples with lower tumor percentage and low amount of the mutated allele, automated Sanger sequence analysis could miss variants, whereas HRM could still detect mutations in gDNA and wgaDNA from samples with low tumor percentages.…”
Section: Discussionmentioning
confidence: 99%
“…58 Recently, studies have demonstrated K-ras mutations in 11% to 40% of esophageal adenocarcinomas, but few data are available on the frequency of Ras mutations in gastric cardia adenocarcinomas. 57,59 Moreover, available data do not support an important role for oncogenic B-raf in adenocarcinomas of the upper gastrointestinal tract. 57,60,61 Given the pivotal role of Ras proteins in the regulation of cell growth, it is not surprising that inhibitors of Ras are in development as anticancer therapies.…”
Section: Independence From Exogenous Stimulationmentioning
confidence: 99%
“…57,59 Moreover, available data do not support an important role for oncogenic B-raf in adenocarcinomas of the upper gastrointestinal tract. 57,60,61 Given the pivotal role of Ras proteins in the regulation of cell growth, it is not surprising that inhibitors of Ras are in development as anticancer therapies. The enzyme farnesyltransferase (FTase) catalyzes the addition of a farnesyl isoprenoid moiety to Ras, a modification which allows Ras to attach to the inner surface of the plasma membrane and trigger cell signaling.…”
Section: Independence From Exogenous Stimulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and experimental studies have shown that point mutation of Kras2 gene plays an important role in the development and progression of tumors [1][2][3][4] . However, it has been reported that wild type Kras2 gene has inhibitory effects on tumor growth and proliferation [5] .…”
Section: Introductionmentioning
confidence: 99%